Actinomycotic osteomyelitis of maxilla in a diabetic patient- "A rare case report & review of literature" - Basavaraj T Bhagawati; Manisha Solanki; Hemlata Solanki; Manish Sharma (Wolters Kluwer Medknow Publications, 2021)
Actinomycosis may be a relatively rare infection caused by saprophytic bacteria of the mouth and alimentary canal which will become pathogenic. The chronic hyperglycemia in Diabetes Mellitus induces events that promote structural changes in various tissues and are related to problems in wound healing. This infection remains largely unknown to most clinicians due to its different presentations, and palatal involvement is extremely rare. This report describes the case of a 50-year-old man who was diagnosed with actinomycosis involving mucosal surface. The main clinical, histopathologic, and therapeutic characteristics and diagnosis of actinomycosis are reviewed. Till date, 4 cases of actinomycosis involving the palatal surface are reported.